In Vitro Exposure Systems and Dosimetry Assessment Tools for Inhaled Tobacco Products: Workshop Proceedings, Conclusions and Paths Forward for In Vitro Model Use. Issue 3 (July 2017) - Behrsing, Holger; Hill, Erin; Raabe, Hans; Tice, Raymond; Fitzpatrick, Suzanne; Devlin, Robert; Pinkerton, Kent; Oberdörster, Günter; Wright, Chris; Wieczorek, Roman; Aufderheide, Michaela; Steiner, Sandro; et al.
In 2009, the passing of the Family Smoking Prevention and Tobacco Control Act facilitated the establishment of the FDA Center for Tobacco Products (CTP), and gave it regulatory authority over the marketing, manufacture and distribution of tobacco products, including those termed 'modified risk'. On 4–6 April 2016, the Institute for In Vitro Sciences, Inc. (IIVS) convened a workshop conference entitled, In Vitro Exposure Systems and Dosimetry Assessment Tools for Inhaled Tobacco Products, to bring together stakeholders representing regulatory agencies, academia and industry to address the research priorities articulated by the FDA CTP. Specific topics were covered to assess the status of current in vitro smoke and aerosol/vapour exposure systems, as well as the various approaches and challenges to quantifying the complex exposures in in vitro pulmonary models developed for evaluating adverse pulmonary events resulting from tobacco product exposures. The four core topics covered were: a) Tobacco Smoke and E-Cigarette Aerosols; b) Air–Liquid Interface- In Vitro Exposure Systems; c) Dosimetry Approaches for Particles and Vapours/ In Vitro Dosimetry Determinations; and d) Exposure Microenvironment/Physiology of Cells. The 2.5-day workshop included presentations from 20 expert speakers, poster sessions, networking discussions, and breakout sessions which identified key findings and provided recommendations to advance these technologies. Here, we will report on the proceedings, recommendations, and outcome of the April 2016 technical workshop, including paths forward for developing and validating non-animal test methods for tobacco product smoke and next generation tobacco product aerosol/vapour exposures. With the recent FDA publication of the final deeming rule for the governance of tobacco products, there is an unprecedented necessity to evaluate a very large number of tobacco-based products and ingredients. The questionable relevance, high cost, and ethical considerations for the use of in vivo testing methods highlight the necessity of robust in vitro approaches to elucidate tobacco-based exposures and how they may lead to pulmonary diseases that contribute to lung exposure-induced mortality worldwide.